APLIKASI INSEKTISIDA NABATI BERBAHAN TANAMAN RAWA DALAM MENGENDALIKAN HAMA SAWI DI LAHAN RAWA PASANG SURUT - Syaiful Asikin; Yuli Lestari (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
Vegetables are also needed by the community as a intake of fresh and healthy food to maintain a healthy body, of the many horticultural plants, green mustard/caisin/mustard (Brassica juncea L.) is one of the horticultural crops of vegetables that use their leaves. who is still young. One of the obstacles in the cultivation of mustard is pests and diseases, as for several types of mustard vegetable pests including: small grasshopper pests, Armyworm (Spodoptera litura, plutella (Plutella xylostella), and (Crocidolomia pavonana) With the level of damage to these plants quite varied between 10-25%, some even cause crop failure.From the results of this study it can be concluded that the kepayang, galam and chirinyuh plants can be used as vegetable pesticides in controlling pests of mustard plants in swamps tides, especially for chirinyuh plants, this chirinyuh plant extracts in addition to functioning as a plant-based pesticide also functions as liquid leaf fertilizer, because the mustard plants show larger and greener plants compared to other plant extracts. Keywords: Application, Botanical Insecticide, Mustard Pest.